Transbouundary aquifers between Slovenia and Croatia - The area bewtween Gulf of Kvarner and Gulf of Trieste - Biondić, Božidar; Prestor, Joerg; Biondić, Ranko; Lapanje, Andrej; Kapelj, Sanja; Janža, Mitja; Rikanovič, Rada; Urbanc, Janko; Singer, Davorin (Geologija, 2002)
Directive 2000/60/EC is defining body of groundwater as a distinct volume of groundwater within an aquifer or aquifers. Every member state has to identify all groundwater bodies where the water is in the certain amount abstracted or where is intent to abstract for water supply. Special significance should be given to those bodies of groundwater that extent across the State borders, i.e. groundwater that has underground flow from one to another side of the State border. In 2000/2001 there was common Slovene-Croatian research project effectuated on the area between Gulf of Kvarner and Gulf of Trieste. In this frame transboundary aquifer systems on this area were identified, the standardized hydrogeological map was produced, tansboundary water divides and theirs uncertainties were identified, common GIS and representative monitoring system were established, additional tracer test was done in Buje anticline area. Transboundary aquifer system in the area between Gulf of Kvarner and Gulf of Trieste are of extreme importance for water supply of cities like Reka (Croatia) and Koper (Slovenia). Future conservation and optimal abstraction of these aquifers where the recharge area is at least partly in one state and abstraction point in the other state mutual research activities are indispensable.